Notes on 2-Normed Spaces Through Their Quotient Spaces - Francis Yunito Rumlawang; Hernita Hernita; Yopi Andry Lesnussa; Harmanus Batkunde (Mathematics Department, Maulana Malik Ibrahim State Islamic University of Malang, 2025)
In this paper, we defined new norms in 2-normed spaces derived from the 2-norm with respect to its quotient spaces. Moreover, these norms were used to observe some aspects of 2-normed spaces namely, a Convergent sequence, a Cauchy sequence, completeness, a closed set, and a bounded set. Furthermore, we used these aspects to prove the Fixed-Point Theorem in a 2-Banach Space.